Clinical case of inhibitor form of hemophilia B in a child - Alexandra V. Serezhkina; Irina G. Khmelevskaya; Natalya S. Razinkova; Irina I. Zhiznevskaya; Tatyana A. Minenkova; Tatyana V. Feoktistova; Maxim P. Ivenkov (LLC "MEDIAFORMAT", 2024)
Hemophilia B is a hereditary, X-linked recessive disease caused by a violation of plasma homeostasis, resulting from a deficiency or absence of coagulation factor IX (FIX). The cause is a mutation of the Xq27 gene encoding FIX. A serious complication of this pathology is the inhibitory form, clinically manifested by the presence of IgG allo-antibodies neutralizing exogenous FIX. The article describes a clinical case of an inhibitory form of hemophilia B in a 12-year-old child.